(untitled) (Medicine Today, 2017)
Acute myocardial infarction (AMI) is a common non - communicable disease prevailing in developed as well as in developing countries like Bangladesh, causing a great number of mortality and morbidity and impart a huge economic burden to family as well as to society. This study was designed to see the various complications and outcome of the patients of AMI, admitted in a tertiary care hospital in Bangladesh. In this observational study, 100 patient of AMI admitted in Cardiology ward of CMCH were enrolled. Clinical diagnosis was made from history and clinical examination and confirmed by ECG and biochemical markers. Informed written consent was taken from the patient or from the patient’s attendant. Among the 100 cases of AMI, 89% were suffering from STEMI and 11% were from NSTEMI. Most of the patients (39%) were in 50-59 years age group. Majority of patient had chest pain (52%), followed by dyspnoea (23%), palpitation 10%, syncopal attack 7% and cardiac arrest 8% respectively. Important risk factors were history of smoking (37%), Diabetes (33%), Hypertension (31%), Dyslipidaemia (21%) and family history of IHD (16%). ECG showed ST-elevation in 80% of patients. It has been revealed that the important complications were cardiogenic shock(31%) followed by acute LVF(21%), bradyarrythmia (12%), tachyarrhythmia (10%), cardiac arrest(8%) and 12% patients died within 24 hours of admission. Patients with AMI have a substantially increased risk of death after hospitalization when shock, LVF or arrhythmias occur during their hospital stay. These complications should have to be treated promptly to achieve a good outcome. Medicine Today 2016 Vol.28(1): 6-8